Kinims / Muhammad 'Imran Hakim Jamilul-Lail - Jamilul-lail, Muhammad 'Imran Hakim (2021)
To begin, I decided to sell Coco Tub from NIMS for my social media portfolio since I have been a customer of theirs since the year 2020. At first, I was only a frequent customer, but after a year, I decided to become an agent since their Coco Tubs are so addicting to consume and perfectly fit my palate also can making money for side income. Aside from that, the demand for this Coco Tub is high since people today prefer to look for something new that can satisfy their sweet appetite, and this Coco TUB is one of the snack foods that will undoubtedly draw people to purchase it because of its unique taste. A gathering of data on the Kinims Facebook Page, which is owned by Muhammad 'Imran Hakim Bin Jamilul-Lail, may be found in this social media portfolio. The business was founded on April 1, 2021, and its headquarters are situated at No 24, Jalan Pulau Indah U10/56A Taman Sandaran Permai 40170 Shah Alam, Selangor. Kinims is a business that sell premium items, such as the Coco Tub, to satisfy people's demand and desires. The Coco Tub are made up of five distinct types of ingredients, which are Coco Crunch, Rice, Ball, Krisp, and Rainbow series, respectively. Kinims Coco Tub by NIMS have always been produced with only the premium chocolate, ensuring that they never fail to satisfy their customers. There have been no sales from any of the posts on the Facebook page, and the owner believes that by establishing this Facebook page, the number of consumers will increase over time and the page will be able to draw in even more customers.